Effect of ozone application on bovine carcasses in abattoir cold chambers - Brusa, Victoria; Restovich, Viviana; Cap, Mariana; Chiapparoli, Virginia; Grigioni, Gabriela Maria; Giannuzzi, Leda; Vaudagna, Sergio Ramon; Leotta, Gerardo Anibal (Public Library of Science ONE (PLoS ONE), 2025)
Different technologies have been evaluated to promote food safety and improve the microbiological quality and shelf life of food. The aim of this work was to determine the effect of gaseous ozone on beef carcass weight loss and indicator microorganism counts in an exporting abattoir. Two gaseous ozone concentrations (3 and 10 ppm) were applied on carcasses from Experiment 1 (Exp. 1, n = 100 test, n = 100 control) and Experiment 2 (Exp. 2, n = 100 test, n = 100 control), respectively. Cold chamber without ozone was used as control in both experiments. For mesophilic aerobic organism (MAO), coliform and Escherichia coli counts, 100 cm2 of each carcass was swabbed before and 10, 20 and 30 h after ozone application. In Exp. 1, the carcass entire surface was swabbed for Shiga-toxin (stx) gene detection. The counts of MAO were influenced by treatment and sampling time in both experiments. In Exp. 1, control carcasses had higher counts than ozonated carcasses at all sampling times, whereas the opposite occurred in Exp. 2. Coliform count was affected by sampling time in Exp. 2, whereas E. coli count was not affected in any experiment. All samples analyzed were stx-negative. Differences in carcass weight loss were not significant. In conclusion, gaseous ozone was not effective to reduce bacterial load or carcass weight loss. To our knowledge, this is the first study evaluating ozone effect on beef carcasses conducted in a commercial abattoir, not at laboratory scale. Future research would help demonstrate whether the use of ozone impacts on the quality and sensory characteristics of beef.